The peculiarities of hyper-hyponimic relations in the military vocabulary of Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the essence of lexical and semantic category of hyponymy is studied, the character of the semantic organization of military vocabulary is analyzed, the main functions of hyponyms and the totality of the formal means of the expression of hyponymic relations are determined.
Keywords: hyponyms; military vocabulary; semantic meaning; kind and type relations